Co integration test for growth and employment of Indian software industry - Philip, Abey (InderScience Publishers, 2014)
The development of the Indian software industry is keenly observed internationally. The Indian software industry could generate employment opportunities for the software and hardware sector, though it is creating more employment opportunities in the informal sector. The study examines the bidirectional relationship between employment and growth of the software industry in India. The tests of unit root and cointegration were applied to check up the time series properties of the data before running the Granger test of causality between the software growth and employment variables such as software and software employment. The results did not produce any evidence to support either the employment led software growth or software growth employment hypothesis in India.